Determination of Relation of Gender Variation in Age and Cardiac Risk Factors in Unstable Angina in Bangladeshi Population (Journal of Chittagong Medical College Teachers' Association, 2012)
The incidence of Unstable Angina is increasing. More than 80% of CAD is attributed to different modifiable cardiac risk factors. Evidence of effect of sex on different cardiac risk factor and as well as effect of age in different sex for CAD is still limited and needs evaluation. An observational case series study conducted on 50 consecutive cases following appropriate inclusion and exclusion criteria in the Department of Physiology, Chittagong Medical College in collaboration with CCU of Chittagong Medical College Hospital from September 2006 to July 2008. The cases of unstable angina were diagnosed on the basis of clinical criteria and ECG findings. Serum Troponin I level were estimated to exclude Non-STE MI. There were statistically significant difference of cardiac risk factors (smoking, hypertension and diabetes mellitus) with sex variation (p value